Modifying playfair cipher algorithm using KAJ spiral method to fit any language regardless of the number of characters - Ibrahim A. Sholi; Mohamad A. Mohamed (Institute of Advanced Engineering and Science, 2019)
In this paper we proposed KAJ Spiral method for supporting PlayFair cipher algorithm to use languages other than English and utilize block with more than two characters at once. Original method does not support block of characters and other languages. The method uses a spiral shape with two axes (X, Y) and the letters are spread on the axis within circles depending on the language. We use Friedman method analysis (index of coincidence) as a tool to test and prove the efficiency of KAJ Spiral method, and we found that it is at least equally secure to the original PlayFair cipher. The aims of this is making cryptography just like mathematics a universal language such that people with different languages can use this algorithm for secure communication, and at the same time make the algorithm stronger and easy to use, with the ability to fit any language.